Fetal and Neonatal Middle Cerebral Artery Hemodynamic Changes and Significance under Ultrasound Detection in Hypertensive Disorder Complicating Pregnancy Patients with Different Severities. (28th June 2022) - Zhou, Pei; Sun, Yi; Tan, Yongpan; An, Yanru; Wang, Xingxing; Wang, Lufang
Abstract : Colour Doppler ultrasound was applied for monitoring the hemodynamic parameters of fetal uterine artery (UtA), umbilical artery (UA), and middle cerebral artery (MCA) during pregnancy. In hypertension disease complicating pregnancy, these hemodynamic measures and their therapeutic applicability value were reviewed (HDCP). 120 singleton pregnant women were chosen, with 40 cases of mild preeclampsia (mild group), 40 cases of severe preeclampsia (severe group), and 40 normal control pregnant women (control group). The hemodynamic parameters of UtA, MCA, and UA were monitored in the three groups, including pulsatility index (PI), resistance index (RI), and the systolic/diastolic velocity (S/D). The parameters PI, RI, S/D, and venous catheter shunt rate (Qdv/Quv) of UtA and UA in the severe group were higher than those in the normal group and the mild group, showing the differences statistically significant (P < 0.05 ). The PI, RI, and S/D of MCA in the severe group were lower than those in the normal group and the mild group (P < 0.05 ). The changing trends of PI, RI, and S/D in the severe group were all first increased and then decreased in the early, middle, and later pregnancy (P < 0.05 ). The area under the curve (AUC) was 0.98 in the receiver operating characteristic (ROC) curve created using a combination of hemodynamic measures and pregnancy outcomes, and the sensitivity and specificity for predicting bad outcomes were 94.7 percent and 96.4 percent, respectively. Colour Doppler ultrasound may accurately detect changes in the PI, RI, and S/D of UtA, MCA, and UA in pregnant women and serve as a reference for determining the intrauterine state of the fetuses and predicting bad pregnancy outcomes. In particular, the parameters in later pregnancy were higher worthy of diagnostic value for adverse pregnancy outcomes. The combination of various parameters could make an improvement of the diagnostic accuracy and provide a basis for guiding treatment as well as determining the optimal timing of delivery.